Business Risks In The Industry Of The Republic Of Uzbekistan (Eurasian Journal of History, Geography and Economics, 2024)
Uzbekistan is increasing its industrial and export potential. The volume of exports of highvalue-added products and their share in the country's total exports are increasing. Dependence on energy and cotton exports is decreasing. The structure of exports of industrial products has changed qualitatively in the direction of increasing exports of finished products. Nevertheless, the potential to increase production and export of finished products with high added value is still not fully exploited